2022
DOI: 10.1017/s1759078722000253
|View full text |Cite
|
Sign up to set email alerts
|

SAR and thermal distribution of pregnant woman and child inside elevator cabin

Abstract: A detailed dosimetry study of electromagnetic absorption and temperature rise under real scenarios is delivered when a mobile phone is used inside an elevator cabin. Numerically accurate human models of a 7th month pregnant woman and a 5-year-old female child are utilized as the exposed subjects. The female child acts as the phone user. The mobile phone is modeled in three talk positions (parallel, tilt, and cheek) operating at 1000 MHz and 1800 MHz. From the obtained numerical results for the specific absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Karatsi et al. (58) investigated the SAR and temperature rise in the tissues of pregnant women and a child using a metallic elevator at 1000 and 1800 MHz ( 91 ) . Their simulation results showed that a child’s exposure was significantly affected by the position of the phone and less affected by the position of the near human body.…”
Section: Detailed Review and Analysismentioning
confidence: 99%
“…Similarly, Karatsi et al. (58) investigated the SAR and temperature rise in the tissues of pregnant women and a child using a metallic elevator at 1000 and 1800 MHz ( 91 ) . Their simulation results showed that a child’s exposure was significantly affected by the position of the phone and less affected by the position of the near human body.…”
Section: Detailed Review and Analysismentioning
confidence: 99%